Icariside I specifically facilitates ATP or nigericin-induced NLRP3 inflammasome activation and causes idiosyncratic hepatotoxicity - Yuan Gao; Guang Xu; Li Ma; Wei Shi; Zhilei Wang; Xiaoyan Zhan; Nan Qin; Tingting He; Yuming Guo; Ming Niu; Jiabo Wang; Zhaofang Bai; et al. (Cell Communication and Signaling, 2021)
Abstract Background Epimedii Folium (EF) is commonly used for treating bone fractures and joint diseases, but the potential hepatotoxicity of EF limits its clinical application. Our previous study confirms that EF could lead to idiosyncratic drug-induced liver injury (IDILI) and hepatocyte apoptosis, but the mechanism remains unknown. Studies have shown that NLRP3 inflammasome plays an important role in the development of various inflammatory diseases such as IDILI. Specific stimulus-induced NLRP3 inflammasome activation may has been a key strategy for lead to liver injury. Therefore, main compounds derived from EF were chosen to test whether the ingredients in EF could activate the NLRP3 inflammasome and to induce IDILI. Methods Bone-marrow-derived macrophages (BMDMs) were treated with Icariside I, and then stimulated with inflammasome stimuli and assayed for the production of caspase-1 and interleukin 1β (IL-1β) and the release of lactate dehydrogenase (LDH). Determination of intracellular potassium, ASC oligomerization as well as reactive oxygen species (ROS) production were used to evaluate the stimulative mechanism of Icariside I on inflammasome activation. Mouse models of NLRP3 diseases were used to test whether Icariside I has hepatocyte apoptosis effects and promoted NLRP3 inflammasome activation in vivo. Results Icariside I specifically enhances NLRP3 inflammasome activation triggered by ATP or nigericin but not SiO2, poly(I:C) or cytosolic LPS. Additionally, Icariside I does not alter the activation of NLRC4 and AIM2 inflammasomes. Mechanically, Icariside I alone does not induce mitochondrial reactive oxygen species (mtROS), which is one of the critical upstream events of NLRP3 inflammasome activation; however, Icariside I increases mtROS production induced by ATP or nigericin but not SiO2. Importantly, Icariside I leads to liver injury and NLRP3 inflammasome activation in an LPS-mediated susceptibility mouse model of IDILI, but the effect of Icariside I is absent in the LPS-mediated mouse model pretreated with MCC950, which is used to mimic knockdown of NLRP3 inflammasome activation. Conclusions Our study reveals that Icariside I specifically facilitates ATP or nigericin-induced NLRP3 inflammasome activation and causes idiosyncratic hepatotoxicity. The findings suggest that Icariside I or EF should be avoided in patients with diseases related to ATP or nigericin-induced NLRP3 inflammasome activation, which may be risk factors for IDILI. Video abstract.